PENERAPAN PIJAT KEHAMILAN TERHADAP PERUBAHAN KUALITAS TIDUR IBU HAMIL TRIMESTER III - Sirait, Lenny Irmawaty; Akhiriyanti, Evi Nur; Herada Putri, Dwita Sari (STIKes Medistra Indonesia, 2022)
The third trimester is pregnancy that starts at the 28th week until the 40th week. In the third trimester, complaints caused by stomach enlargement, physiological change, and hormonal changes will cause complaints to pregnant women. These complaints include back pain, leg cramps, abdominal discomfort, frequent urination, and 2sleep disturbances that are often experienced by pregnant women, even though their pregnancy is normal, sleep disorders are also often associated with depression in pregnant women. Pregnancy massage can be a solution for pregnant women who experience decreased sleep quality.Purpose: This study is a literature review that aims to examine various studies related to the application of pregnancy massage to changes in sleep quality for pregnant women in the third trimester.Method: The method of this article is a form of metadata analysis research using literature studies with the source used in the electronic database is Google Scholar using the keywords